INFLUENCE OF THE LONGITUDINAL AND TRANSVERSE DISPLACEMENT OF THE CARGO GRAVITY CENTER IN GONDOLA CARS ON THEIR DYNAMIC INDICATORS - Shvets, A. O. (Science and Transport Progress, 2018)
Purpose. Increase in the movement speed of railway vehicles makes it possible to strengthen integration processes with the countries of Europe and Asia and leads to the need to improve control, to quantify the dynamic load of rolling stock to ensure safe and reliable communication on the railways. Therefore, in the process of design and operation of rolling stock, the quantitative assessment of dynamic loads constitutes an urgent scientific and technical task. The purpose of this paper is to investigate the effect of longitudinal and transverse displacement of the cargo gravity center in gondola cars during movement speed increase on their main dynamic indicators –the horizontal and vertical dynamics coefficients, the derailment stability coefficient. Methodology. The study was carried out by the method of mathematical and computer simulation of the dynamic loading of freight gondola car using the model of spatial oscillations of the five cars coupling and the software complex developed in the branch research laboratory of dynamics and strength of rolling stock (BRL DSRS) of the Dnepropetrovsk National University of Railway Transport named after Academician V. Lazaryan. Theoretical studies were carried out during the movement of the 12-532 gondola car model with typical bogies 18-100 with speeds in the range from 50 to 90 km/h in curves with radii of 350 and 600 m, with increases of the outer rail 130 and 120 mm, respectively. Findings. The article presents analysis of the carried out theoretical researches of dynamic qualities of rolling stock using the example of gondola cars. Calculations are performed using the package of applied programs with sufficient accuracy for practice. When performing the theoretical studies and after modeling, taking into account the processes of oscillation of the freight car and cargo at the longitudinal and transverse displacement of its gravity center in the gondola car, the dependences of the main dynamic parameters taking into account the movement speed were obtained. Originality. The article investigates the effect of longitudinal and transverse displacement of the load’s gravity center on the dynamic loading of the car in order to solve the problem of forecasting the rolling stock dynamics. The results of theoretical studies taking into account the movement speed in curved track sections of small and medium radius. Practical value. The article has a practical focus. Application of the results will contribute to improving the traffic safety of freight cars and will improve the technical and economic performance of the railway transport.